Exploring Indonesian EFL Teachers' Tension during the Transition of Online to Offline Learning - Dewanty, Monika; Kuswandono, Paulus (Language Circle: Journal of Language and Literature, 2022)
Since the outbreak of Covid-19, novice teachers have experienced considerable challenges and transformation to cope with such abrupt changes. This study aims to know the tension that novice teachers encountered during the transition of the Covid-19 Pandemic. The teaching-learning activity has now been shifting from the online class to the blended class and now to offline classes under some conditions. The method employed in this research was a qualitative method using open-ended questionnaires and interviews. The participants of this research were 5 novice teachers that first became a teacher during the pandemic. The study shows that novice teachers’ tensions were influenced by personal factors, interpersonal factors, and organizational factors. To conclude, the intervention of all members of the school is important to make good teaching-learning activities.